Income per capita and government healthcare financing in Sub-Saharan Africa: The moderating effect of indebtedness - Tamisai Chipunza; Lungile Ntsalaze (Scientific African)
The study investigated the moderating role of public indebtedness on the relationship between per capita income and government healthcare financing in Sub-Saharan Africa (SSA). Based on panel data for 35 SSA countries over the period 2010 – 2020, the panel quantile Autoregressive Distributed Lag (ARDL) model with dynamic fixed effects was applied. Robustness analysis was performed using the panel Fully Modified Ordinary Least Squares (FMOLS) approach. It was established that income per capita positively influenced per capita government health spending while the debt burden had a negative effect. The coefficient for the interaction term was negative and significant, affirming the hypothesis that indebtedness distorts the positive impact of per capita income on government healthcare financing. To mitigate the adverse effects of indebtedness on healthcare financing, there is a need for SSA countries to maintain public debt at appropriate levels and allocate borrowed funds to projects that stimulate economic growth.